Tuberculous Laryngitis Mimicking Residual Glottic Carcinoma in COVID-19 Patient - Rahim, Norazila Abdul; Baki, Marina Mat (International Journal of Human and Health Sciences (IJHHS), 2022)
We presented a case of a 67-year-old Malay gentleman who underwent transoral laser microsurgery and type VI cordectomy in July 2021 for glottic carcinoma involving anterior commissure and bilateral anterior 1/3 of vocal folds (T2N0M0). Two weeks following the surgical procedure, the patient was diagnosed with COVID-19 (Category 2) with a chief complaint of anosmia which delayed the initial postoperative follow-up. The histopathological examination was reported as welldifferentiated squamous cell carcinoma with no evidence of malignancy on the surgical margins. On subsequent visit six weeks postoperatively, video endoscopy of the larynx showed irregular round mass occupying the anterior commissure, bilateral anterior 1/3 of the vocal folds and extending minimally into the subglottic region, hence a residual tumour or granuloma was suspected. The patient was subjected to direct laryngoscopy and biopsy of the mass under general anaesthesia. Intraoperative findings revealed that the mass is soft and friable to palpation, which favours granuloma rather than residual tumour. Histopathology examination showed acid-fast bacilli within the granulomas and the presence of multinucleated giant cells. The final diagnosis was necrotizing granulomatous inflammation favouring mycobacterial infection of the larynx. The patient was referred to the respiratory team for further management of laryngeal tuberculosis and was started on anti-tuberculosis (anti-TB) medications immediately. During one month of surveillance following anti-TB treatment, there was no mass seen at the anterior commissure, which indicates a good response to anti-TB treatment. Despite a high residual rate of glottic carcinoma involving anterior commissure, laryngeal tuberculosis cannot be excluded, especially in an immunocompromised patient. Thus, prompt diagnosis and early referral to the respective team are essential in managing the patient. International Journal of Human and Health Sciences Supplementary Issue: 2022 Page: S34